Evaluation of energy properties of torrefied biomass for a given pyrolysis condition by isothermal pyrolysis kinetics - Fumiya MORIYAMA (The Japan Society of Mechanical Engineers, 2021)
One of the effective solutions to reduce CO2 emission derived from fossil fuels is the suppression of coal consumption in industrial boilers and power plants. Torrefaction is one of the promising treatments for reforming conventional solid biofuels, and torrefied solid biofuels have come to attract attention as an alternative to coal. When torrefied solid biofuels are utilized or produced, energy properties such as higher heating value (HHV) and energy yield of torrefied solid biofuels are quite important. In this study, to evaluate the energy properties for a given pyrolysis condition analytically, evaluation methods of HHV and mass yield of torrefied biomass based on isothermal pyrolysis kinetics are investigated for three biomass species, i) softwood; Japanese cedar, ii) hardwood; castanopsis and iii) herbaceous biomass; rice straw. There are two aims of the study. One is to present the HHV evaluation method by lumped-parameter pyrolysis kinetic models with high evaluation accuracy. The reduction in the mass yield due to torrefaction can be evaluated by the two-step pyrolysis kinetic model, and the HHV is provided with the mass fractions and heating values for constituent substances included in torrefied biomass of the two-step pyrolysis kinetic model. The other is to present the simple correlation to evaluate HHV without depending on three biomass species. From the comparison between the HHV evaluation method and experimental data, it is clarified that the proposed HHV evaluation method based on the two-step pyrolysis kinetic model can be useful to evaluate the HHV of torrefied biomass for three biomass samples with high evaluation accuracy, 5% or less. The linear correlation between HHV enhancement factor and mass yield of torrefied biomass is found regardless of three biomass species in the range of torrefaction mass yield larger than 0.6.